Indirect effects of bioinvasions in Yellowstone Lake: The response of river otters to declines in native cutthroat trout. (November 2015) - Crait, Jamie R.; Regehr, Eric V.; Ben-David, Merav
Abstract: Nonnative species threaten ecosystems throughout the world — including protected reserves. In Yellowstone National Park, river otters Lontra canadensis depend on native cutthroat trout as prey. However, nonnative lake trout and whirling disease have significantly reduced the abundance of these native fish in the park's largest body of water, Yellowstone Lake. We studied the demographic and behavioral responses of otters to declining cutthroat trout on Yellowstone Lake and its tributaries. From 2002-2008, we monitored otter activity at latrine (scent-marking) sites, collected scat for prey identification, and used individual genotypes from scat and hair samples to evaluate survival and abundance with capture–recapture methods. Otter activity at latrines decreased with declines in cutthroat trout, and the prevalence of these fish in otter scat declined from 73% to 53%. Cutthroat trout numbers were the best predictor of temporal variation in apparent survival, and mean annual survival for otters was low (0.72). The density of otters in our study area (1 otter per 13.4 km of shoreline) was also low, and evidence of a recent genetic bottleneck suggests that otter abundance might have declined prior to our study. River otters in and around Yellowstone Lake appear to be responding to reductions in cutthroat trout via changes in distribution, diet, and possibly survival and abundance. Our results provide a baseline estimate for monitoring the broader outcome of management efforts to conserve native cutthroat trout and emphasize the indirect ecosystem consequences of invasive species. Highlights: Invasive species are negatively affecting native cutthroat trout in Yellowstone Lake We assessed the effects of declining cutthroat trout on river otters Otter abundance was stable but survival was correlated with spawning trout Otter activity and consumption of trout declined with the fish during the study The influence of bioinvasions may extend beyond Yellowstone Lake, emphasizing the importance of continued management.